Development Of Physical Education And Health Learning Management System Through Si Pojok Application At Sd Negeri 2 Pakis Kemba - Rizaldis, Muhammad Jerit Aldo; Nurabadi, Ahmad (Proceedings Series of Educational Studies, 2025)
In the learning process requires a good system to be able to implement good, structured and systematic learning materials. The development of a Learning Management System is an effective step to achieve good learning quality, especially in physical education and health materials. The purpose of this study is to develop a learning management system through the sipojok application, with this development it is expected that the learning system can be more effective so that children's learning achievements are expected to increase. The method applied in this research and development is the development model from Borg and Gall, namely: 1) Determining the research problem 2) Collecting Information (a) Reviewing the bibliography (b) Needs Analysis (3) Initial product design and Validation (4) Small group trials (5) revision (6) Field trials (7) Final product of research and development. The results of this study are in the form of the sipojok application, based on this research and development it is expected that the product of this research and development in the form of a learning management system can be applied in the learning process at SD Negeri 2 Pakis Kembar.